GER-ANIUM - Jonathan Flacker (Association of American Medical Colleges, 2010)
Abstract This resource is a small-group interactive educational toll loosely based on the game "Cranium." It demonstrates proficiency in topics with a focus on outpatient geriatric medicine content. At our institution, a session takes place with four to six internal medicine residents and runs 90 minutes. During that time, residents make it through most, though not all, of the 50 cards in the set. The game begins by having a resident select any card from the GER-ANIUM stack, which has been shuffled so that the cards are randomly arranged. Each card instructs the resident to complete a task in one of four categories: a drawing or sculpting task, a task requiring core knowledge or formulas, a task requiring physical demonstration of the answer, or a task that must be completed by the whole group rather than any one player. Play proceeds around the table. For each answer given, a faculty moderator assigns a point value of 1-5. At the end, the residents add up their scores, and a winner is declared. Effectiveness is anecdotal since the resource is just one 90-minute session during the month-long geriatrics rotation. However, multiple comments from residents, both written and verbal, include the following: "This is great! You should sell it. All learning should be like this," and "That was really fun."